AN INFLUENCE OF ENDORPHIN MASSAGE ON THE IMPROVEMENT OF BREASTFEEDING PRODUCTION TO MOTHERS WHO DETECT POST PARTUM BLUES BY EDINBURGH POST PARTUM DEPRESSION SCALE (EPDS) SCREENING AT COMMUNITY HEALTH CENTER AROUND MATARAM - Baiq Eka Putri Saudia; Ni Nengah Arini Murni (poltekkes kemenkes mataram, 2017)
Abstract : Post partum blues is phenomenon which occurs at the first week of postpartum, the peak of symptoms occurs on third to seventh day of postpartum with duration several hours to several days. Postpartum blues are categorized as mild mental disorders thus it often ignored, undiagnosed, and finaly untreated, this situation will create uncomfortable feelings for women who suffer from it, thus the impact gets worse and continue to postpartum depression. Postpartum blues can be detected by EPDS screening. One of the techniques to prevent the occurance of postpartum blues is endorphin massage which is a technique of touch and light massage. The research objective was to find out the effect of endorphin massage on the improvement of exclusive breastfeeding and the decrease of EPDS on mothers who detected postpartum blues. The research was pre experimental with an approach of non randomized control group pre-post test or non equivalen control group design. The sample was determined by purposive sampling. The research was conducted at community health center around Mataram for 5 months (June-October) in 2016. The total sample was 20 mothers with postpartum blues who were treated, and 20 mothers were in the control group. Mothers who detected postpartum blues would be examined their exclusive breastfeeding production by assesse the indicator from infant’s factors used observational questionnaire before and after conducting treatment. The treatment was endorphin massage that given as many as 5 times by researceher since the third day to seventh day after labor. The second assessment of breastfeeding production was done immediately after the fourth treatment to determine the increasing of breastfeeding production after given endorphin massage. The collected data was analyzed by using statistical analysis with SPSS. The findings was there was a significance influence of endorphin massage on the improvement of breastfeeding (p=0.000) and the decrease of EPDS score (p=0.000). The conclusion is endorphine massage can be alternative theraphy which is effective in increasing breastfeeding production and postpartum management. The results of this study concluded, endorphin massage can be used as an effective alternative therapy in increasing milk production and postpartum blues management.